Elp1 is required for development of visceral sensory peripheral and central circuitry - Zariah Tolman; Marta Chaverra; Lynn George; Frances Lefcort (The Company of Biologists, 2022)
Cardiovascular instability and a blunted respiratory drive in hypoxic conditions are hallmark features of the genetic sensory and autonomic neuropathy, familial dysautonomia (FD). FD results from a mutation in the gene ELP1, the encoded protein of which is a scaffolding subunit of the six-subunit Elongator complex. In mice, we and others have shown that Elp1 is essential for the normal development of neural crest-derived dorsal root ganglia sensory neurons. Whether Elp1 is also required for development of ectodermal placode-derived visceral sensory receptors, which are required for normal baroreception and chemosensory responses, has not been investigated. Using mouse models for FD, we here show that the entire circuitry underlying baroreception and chemoreception is impaired due to a requirement for Elp1 in the visceral sensory neuron ganglia, as well as for normal peripheral target innervation, and in their central nervous system synaptic partners in the medulla. Thus, Elp1 is required in both placode- and neural crest-derived sensory neurons, and its reduction aborts the normal development of neuronal circuitry essential for autonomic homeostasis and interoception. This article has an associated First Person interview with the first author of the paper.